Socialism and the Jewish Community in Slovakia - Salner, Peter (Studia Etnologiczne i Antropologiczne, 2020)
This study is based on data acquired by the oral history method and discusses the reflections of two generations of Jews in relation to the socialist regime in Czechoslovakia (1948–1989). The first generation is represented by people who had survived the Holocaust. The second generation is represented by the ‘children of the Holocaust’ (born 1945–1965). They grew up at a time when the political realm was completely dominated by the Communist Party. Their attitudes only changed with the invasion of Czechoslovakia in August 1968. This probe suggests differences which stem from contrasting life experiences.